Referrals between Public Sector Health Institutions for Women with Obstetric High Risk, Complications, or Emergencies in India - A Systematic Review. - Samiksha Singh; Pat Doyle; Oona M Campbell; Manu Mathew; G V S Murthy (PLoS ONE)
Emergency obstetric care (EmOC) within primary health care systems requires a linked referral system to be effective in reducing maternal death. This systematic review aimed to summarize evidence on the proportion of referrals between institutions during pregnancy and delivery, and the factors affecting referrals, in India. We searched 6 electronic databases, reviewed four regional databases and repositories, and relevant program reports from India published between 1994 and 2013. All types of study or reports (except editorials, comments and letters) which reported on institution-referrals (out-referral or in-referral) for obstetric care were included. Results were synthesized on the proportion and the reasons for referral, and factors affecting referrals. Of the 11,346 articles identified by the search, we included 232 articles in the full text review and extracted data from 16 studies that met our inclusion criteria Of the 16, one was RCT, seven intervention cohort (without controls), six cross-sectional, and three qualitative studies. Bias and quality of studies were reported. Between 25% and 52% of all pregnancies were referred from Sub-centres for antenatal high-risk, 14% to 36% from nurse run delivery or basic EmOC centres for complications or emergencies, and 2 to 7% were referred from doctor run basic EmOC centres for specialist care at comprehensive EmOC centres. Problems identified with referrals from peripheral health centres included low skills and confidence of staff, reluctance to induce labour, confusion over the clinical criteria for referral, non-uniform standards of care at referral institutions, a tendency to by-pass middle level institutions, a lack of referral communication and supervision, and poor compliance. The high proportion of referrals from peripheral health centers reflects the lack of appropriate clinical guidelines, processes, and skills for obstetric care and referral in India. This, combined with inadequate referral communication and low compliance, is likely to contribute to gaps and delays in the provision of emergency obstetric care.